Frederick the Great and the Seven Years' War, 1756-1763 - Redman, Herbert J. (McFarland & Company, Inc., Publishers, 2014)
"A major player in The Seven Years' War (1756-1763), the first true world war, was Frederick the Great, king of Prussia. The first major work on Frederick the Great and his role in the war for more than a century, this book will undoubtedly shed light on many aspects of military and European history"--